Memorandum of Understanding between the University of Ottawa and BRAC University (2010) - University of Ottawa; BRAC University (University of Ottawa and BRAC University, 2013)
Agreement between the University of Ottawa and BRAC University considering - 1. that the University of Ottawa, Canada and BRAC University, Bangladesh, have areas of common interest and similar academic goals in teaching; and 2. that the both institutions are interested in establishing links to strengthen their areas of common interest;